1996
DOI: 10.1177/0306624x96401003
|View full text |Cite
|
Sign up to set email alerts
|

Axis II Comorbidity in Forensic Patients with Antisocial Personality Disorder

Abstract: The authors tested J. S. Wulach's suggestion that the criminal personality is a quadruple personality disorder (PD) consisting of antisocial, borderline, histrionic, and narcissistic PDs. First, forensic patients with antisocial PD were compared to patients without PD using the Millon Clinical Multiaxial Inventory-II (MCMI-II). Second, mean MCMI-II PD scale scores of the antisocial group were examined for clinical significance. Lastly, correlations between the Antisocial scale and all other PD scales of the MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…These findings give, to some extent, support to Wulach's (1988) concept of a criminal personality and psychopathy that comprises the traits of the antisocial, borderline, narcissistic, and histrionic PD. As in the study of male forensic patients by Hillbrand et al, (1996), borderline and narcissistic pathologies were found to coexist in antisocial individuals, but the histrionic pathology support was lacking. In a study of gender differences (Hamburger, Lillienfield & Hogbon, 1996), psychopathic women were found to have more histrionic traits than men, whereas psychopathic men had more antisocial traits than women.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These findings give, to some extent, support to Wulach's (1988) concept of a criminal personality and psychopathy that comprises the traits of the antisocial, borderline, narcissistic, and histrionic PD. As in the study of male forensic patients by Hillbrand et al, (1996), borderline and narcissistic pathologies were found to coexist in antisocial individuals, but the histrionic pathology support was lacking. In a study of gender differences (Hamburger, Lillienfield & Hogbon, 1996), psychopathic women were found to have more histrionic traits than men, whereas psychopathic men had more antisocial traits than women.…”
Section: Discussionmentioning
confidence: 98%
“…In a group of male forensic inpatients with antisocial PD in the United States, high rates of avoidant, borderline, and passive-aggressive personality pathology were reported using the Millon Clinical Multiaxial Inventory-II (MCMI-II) (Hillbrand, Kozmon, & Nelson, 1996).…”
mentioning
confidence: 99%